Stratabound ore deposits of Hualgayoc, Cajamarca, Peru - Canchaya Moya, Samuel (1990)
Hualgayoc is one of the typical "complex mining districts" of the Central Andes, characterized by the influence of many superimposed geologic events and ore-forming processes It has been worked since Spanish colonial times. Initially, Hualgayoc was famous for the silver ores which were extracted principally from the upper parts of the ore deposits. The zones of oxidation and supergene enrichment of many deposits have already been removed by early mining. With time, the production of the district became more polymetallic (zinc, lead, and copper as well as silver). Many mines are being operated by several small companies and some mining ventures of the "mediana mineria". There are up to five flotation plants, with a total capacity of about 800 t/day. Although this important mining district has been the object of a large number of geologic studies by many geologists, we are far from understanding the origin of many of its ore deposits, especially those of the stratabound type. The purpose of this chapter is to describe the geologic, mineralogic and geo- metric characteristics of the stratabound ore deposits of this important district to improve our understanding of the complicated geologic setting of the "mantos". Hualgayoc is situated in northern Peru, at a height of between 3500 m and 2400 m, near, and on the east zone of the continental divide of the Cordillera Occidental.